Dual polarization discrete changes model of inter-core crosstalk in multi-core fibers - Soeiro, R. O. J. (2018)
The discrete changes model (DCM) of inter-core crosstalk (ICXT) in weakly-coupled homogeneous multi-core fibers (MCFs) is generalized to a dual polarization (DP) scheme. This model provides theoretical expressions for the two polarization fields of the ICXT at the MCF output. Therefore, it may be of particular interest in the design of direct-detection MCF systems, where the photodetected ICXT results mainly from the beating between the ICXT field at the MCF output and the carrier of the interfered core. The DP-DCM is validated by comparison of the mean ICXT power and ICXT field amplitude estimates with the ones obtained with a rigorous, yet much more computationally demanding, model based on the coupled local mode theory (CLMT). Good agreement between the mean ICXT power estimates obtained with the DP-DCM and CLMT is observed when the inter-core coupling coefficient variation along the MCF is small. Good agreement is also observed when comparing the probability density functions of the ICXT field amplitude.